The Role of Environmental Awareness and Green Product Literacy on Green Purchase Behavior in Indonesia - A. Nurul Suci Amaliah; Mardiatul Jannah; Muhammad Taufan Gunawan (CV. Sakura Digital Nusantara, 2023)
Consumers consumption pattern is the focal point to reach sustainable development goals. Green purchase become one of actual action to mitigate negative impact of the environmental degradation. In order to protect the environment, consumers shifting into sustainable living era and forms a new market segment called green consumers. Recently, green purchase and green consumers become popular attribute to explore and investigate in consumer research. This study identified potential factors affecting green products purchase as consumer actual behavior. The main predictors environmental awareness and green product literacy, green product literacy also using for moderating effect. Research conducted with a survey and a purposive sampling method, using SEM PLS for data analyzed. The number of valid observations for the data analysis is 100. Based on direct hypothesis testing, it was found environmental awareness finding as a significant factor influencing green purchase behavior. Similarly, the direct effect of green product literacy was found to be as significant factor that influences green purchase behavior. Meanwhile, green product literacy has no moderating effect on the relation between environmental awareness to green purchase behavior. In this way, it will help policymakers and managers for formulating strategy to green consumers, especially in Indonesia.